A study on mid-panel of steel shear-walls with dual openings. (November 2021) - Zabihi, Salaheddin; Mamazizi, Arman; Ghanbari-Ghazijahani, Tohid
Abstract: The presence of openings in steel shear-walls is oftentimes necessary due to different design requirements. This paper investigates the behaviour of a panel in between two openings (mid-panel or MP) in shear-walls with dual openings under monotonic loading. The panel is analogised to link-beams in eccentrically-braced frames. To examine the structural response of these structures, two established conditions (elastic force and displacement) are addressed. Theoretical formulations are developed for a new condition (flexural stiffness of stiffeners to shear stiffness of a plate) in addition to the two conditions above. Furthermore, an equation was derived to calculate the shape factor of sections with box-shaped flanges, which is used to obtain the shear displacement (yield) of the mid-panel's plate. A comprehensive parametric study (44 models) is conducted using Finite Element Analysis (FEA) to examine the effect of six different geometric factors on the structural response of the mid-panel. The mid-panel's dominant structural responses (deformation and stress distribution) are classified as (i) flexural, (ii) shear, and (iii) combined (shear-flexure). The increase of the MP's width, the box-stiffeners' web height, flange's width and thickness causes a shear response, while the increase of the MP's height and the thickness leads to a flexural behaviour. Each structural response is carefully addressed theoretically and numerically leading to consistent results. The variables of the MP's plate bring about higher effects on the behaviour of the MP comparing to the parameters of the stiffeners. Overall, a shear response is structurally desirable, which enhances the MP's energy dissipation and post-buckling capacity. Graphical abstract: Unlabelled Image Highlights: This paper investigates the behaviour of a panel between two openings (mid-panel). A new condition was flexural stiffness of stiffeners to shear stiffness of a plate. An equation was derived to calculate the shape factor of sections with box-shaped flanges. The MP's plate produces higher effects comparing to parameters of the stiffeners. A shear response is desirable, which improves the MP's post-buckling capacity.